Programa computacional interactivo utilizando la técnica de hardy cross para el análisis de red de tuberías (sistemas con tres o más ramas) - Avalos Torres, Roberto Daniel (2006)
Most of the problems concerning the fluids flow in conduits and tubes they imply the prediction of the conditions in a section of a system, when the conditions of some other section are known. In any section of this system, generally we are worried about the pressure of the fluid, the speed of the flow and the elevation of the section. In a line of pipe in series the loss of total energy is the sum of the great and small individual losses. This affirmation is in agreement with the principle of which the equation of the energy is a way to both take into account all the energy in the system between points. The nature parallel systems requires that the technique used for their analysis is different from which is used in series in the analysis of the systems. In general, a parallel system can have any number of branches. It stops most of the problems of this type, the objective is to determine what amount of flow appears in each one of the branches and what pressure fall appears between two sections of the system. The height of excellent programming languages and the availability every greater time of machines computers of high speed, has caused that the techniques of resolution of flowed problems of flow of have been simplified. The importance of the design and suitable selection of pipes in the design of plants and construction of the same ones is so great that many companies have tried to complete a computer system to make the work of design; reason why, the application of sofware interactive “redes_3”, using the technique of Hardy Cross, allows to make the analysis of network of pipes